Type II endoleaks: diagnosis and treatment algorithm - Bryce, Yolanda; Schiro, Brian; Cooper, Kyle; Ganguli, Suvranu; Khayat, Mamdouh; Lam, Cuong (Ken); Oklu, Rahmi; Vatakencherry, Geogy; Gandhi, Ripal T. (Cardiovascular Diagnosis and Therapy; Vol 8, Supplement 1 (April 13, 2018): Cardiovascular Diagnosis and Therapy (Advanced aortic imaging and intervention), 2017)
Elective abdominal aortic aneurysm (AAA) repair is recommended for aneurysms greater than 5.5 cm, symptomatic, or rapidly expanding more than 0.5 cm in 6 months. Seventy-five percent of AAAs today are treated with endovascular aneurysm repair (EVAR) rather than open repair. This is fostered by the lower periprocedural mortality, complications, and length of hospital stay associated with EVAR. However, some studies have demonstrated EVAR to result in higher reintervention rates than with open repair, largely due to endoleaks. Type II is the most common, making up 10–25% of all endoleaks. Type II endoleaks, can potentially enlarge and pressurize the aneurysm sac with a risk of rupture. However, many type II endoleaks spontaneously resolve or never lead to sac enlargement. Imaging surveillance and approaches to management of type II endoleaks are reviewed here.